2009
DOI: 10.1021/om900225x
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Ligand Exchange Reaction of Iron(IV) Complexes with Two Different Group 14 Element Ligands, Cp(CO)FeH(EEt3)(E′Et3) (E, E′ = Si, Ge, Sn)

Abstract: Iron(IV) complexes with two different group 14 element ligands, Cp(CO)FeH(EEt 3 )(E 0 Et 3 ) (E, E 0 = Si, Ge, Sn), were synthesized in the reaction of Cp(CO)Fe (EEt 3 )(py) with Et 3 E 0 H through an appropriate selection of E and E 0 . Systematic ligand exchange experiments of the group 14 element ligand revealed that the reductive elimination of silyl and hydrido ligands occurs more readily than that of germyl and hydrido ligands, and the Fe-Sn bond was not converted into an Fe-Si or Fe-Ge bond at 60 °C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 52 publications
4
9
0
Order By: Relevance
“…In addition, we explored the reaction between CpFe(CO)(SiMe 3 ) ( 3 A ) and Me 3 SiH, and the formation of the oxidative addition product CpFe(CO)(H)(SiMe 3 ) 2 is slightly exergonic by 0.8 kcal mol –1 . This is in good agreement with the experimental fact that CpFe(CO)H(SiEt 3 ) 2 is in equilibrium with the reductive elimination products HSiEt 3 and CpFe(CO)(SiEt 3 ) …”
Section: Resultssupporting
confidence: 91%
“…In addition, we explored the reaction between CpFe(CO)(SiMe 3 ) ( 3 A ) and Me 3 SiH, and the formation of the oxidative addition product CpFe(CO)(H)(SiMe 3 ) 2 is slightly exergonic by 0.8 kcal mol –1 . This is in good agreement with the experimental fact that CpFe(CO)H(SiEt 3 ) 2 is in equilibrium with the reductive elimination products HSiEt 3 and CpFe(CO)(SiEt 3 ) …”
Section: Resultssupporting
confidence: 91%
“…The IR spectrum showed two intense absorption bands at 1949 and 1975 cm −1 attributed to νCO and νC≡C, respectively. The absorption band assignable to νCO is comparable to those reported for Cp‐substituted Cp(OC)FeH(ER 3 )(E'R 3 ) complexes (1901–1946 cm −1 ) [20b–c] . This result indicates that the electron density on the iron center in complex 6 is similar to those of Cp(OC)FeH(ER 3 )(E'R 3 ) complexes, and thus the electron‐donating abilities of Cp*, η 1 ‐alkynyl, and gallyl ligands and Cp, ER 3 , and E'R 3 ligands are similar.…”
Section: Resultssupporting
confidence: 74%
“…The Ge-Fe-Ge angle of 1 (134.77(4) • ) is comparable to the analogous Si-Fe-Si angle in the silicon analogue 2 (135.23 3• ). The Fe-Ge bond is slightly elongated (2.5589(8) Å) compared to those of previously reported iron-organogermyl complexes [17][18][19][22][23][24][25][26]. In the 1 H NMR spectrum of 1, a broad singlet assignable to the SiMe 3 group appeared at 8.67 ppm, and two broad signals corresponding to two molecules of THF coordinated to the iron center were observed at 24.02 and 29.42 ppm, respectively.…”
Section: Scheme 1 Synthesis Of Iron-digermyl Complexmentioning
confidence: 52%
“…For instance, Iwasawa and Takaya have examined the catalytic activity of Pd complexes that bear PSiP or PGeP pincer-type ligands in the hydrocarboxylation of allenes, and found that the latter exhibit superior catalytic performance relative to the former [13][14][15]. However, examples of iron complexes that contain heavier-group-14 ligands, such as organogermyl ligands, remain scarce due to a lack of synthetic methods [16][17][18][19][20]. Most iron-organogermyl complexes have been obtained from the reactions of an iron precursor with organogermanes that bear Ge-H moieties; however, coordinatively saturated species are often formed via this route.…”
Section: Introductionmentioning
confidence: 99%